THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY IN IMPLEMENTING COMPANY BUSINESS - Abdul Rasyid (Sean Institute, 2023)
In the context of a more globalized and fiercely competitive epoch, corporations encounter mounting expectations to not just attain financial gains, but also to actively contribute towards the realms of social and environmental sustainability. In light of these requisitions, numerous corporations have implemented diverse Corporate Social Responsibility (CSR) endeavors. The objective of this study is to examine the impact of Corporate Social Responsibility (CSR) on a company's business practices. This research methodology entails the collection of qualitative data through the utilization of descriptive methodologies. The findings of this study demonstrate the significant impact of Corporate Social Responsibility (CSR) on organizational operations, yielding a multitude of advantages encompassing environmental conservation, poverty alleviation, enhancement of corporate image, cultivation of stakeholder relationships, attainment of competitive edge, and overall improvement in business performance. In its entirety. Effective implementation of corporate social responsibility (CSR) is guided by key principles, including accountability, transparency, and sustainability. This study emphasizes that corporate social responsibility (CSR) encompasses more than just moral obligation; it is also a strategic approach to establishing a sustainable company that generates positive societal outcomes and is prepared to navigate the complexities of an evolving business landscape that prioritizes ethics and sustainability.